Letter to the Editor: Murray Valley encephalitis - Bennett, Noel M (Communicable Diseases Intelligence, 2001)
This article published in Communicable Diseases Intelligence Volume 25, No 3, August 2001 contains a letter to the Editor commenting on the article Murray Valley encephalitis virus surveillance and control initiatives in Australia published in the April issue of CDI.